The efficacy of psychotherapies and pharmacotherapies for mental disorders in adults: An umbrella review and meta‐analytic evaluation of recent meta‐analyses - Leichsenring, Falk; Steinert, Christiane; Rabung, Sven; Ioannidis, John P. A. (World Psychiatry, 2022)
Mental disorders represent a worldwide public health concern. Psychotherapies and pharmacotherapies are recommended as first line treatments. However, evidence has emerged that their efficacy may be overestimated, due to a variety of shortcomings in clinical trials (e.g., publication bias, weak control conditions such as waiting list). We performed an umbrella review of recent meta‐analyses of randomized controlled trials (RCTs) of psychotherapies and pharmacotherapies for the main mental disorders in adults. We selected meta‐analyses that formally assessed risk of bias or quality of studies, excluded weak comparators, and used effect sizes for target symptoms as primary outcome. We searched PubMed and PsycINFO and individual records of the Cochrane Library for meta‐analyses published between January 2014 and March 2021 comparing psychotherapies or pharmacotherapies with placebo or treatment‐as‐usual (TAU), or psychotherapies vs. pharmacotherapies head‐to‐head, or the combination of psychotherapy with pharmacotherapy to either monotherapy. One hundred and two meta‐analyses, encompassing 3,782 RCTs and 650,514 patients, were included, covering depressive disorders, anxiety disorders, post‐traumatic stress disorder, obsessive‐compulsive disorder, somatoform disorders, eating disorders, attention‐deficit/hyperactivity disorder, substance use disorders, insomnia, schizophrenia spectrum disorders, and bipolar disorder. Across disorders and treatments, the majority of effect sizes for target symptoms were small. A random effect meta‐analytic evaluation of the effect sizes reported by the largest meta‐analyses per disorder yielded a standardized mean difference (SMD) of 0.34 (95% CI: 0.26‐0.42) for psychotherapies and 0.36 (95% CI: 0.32‐0.41) for pharmacotherapies compared with placebo or TAU. The SMD for head‐to‐head comparisons of psychotherapies vs. pharmacotherapies was 0.11 (95% CI: –0.05 to 0.26). The SMD for the combined treatment compared with either monotherapy was 0.31 (95% CI: 0.19‐0.44). Risk of bias was often high. After more than half a century of research, thousands of RCTs and millions of invested funds, the effect sizes of psychotherapies and pharmacotherapies for mental disorders are limited, suggesting a ceiling effect for treatment research as presently conducted. A paradigm shift in research seems to be required to achieve further progress. (PsycInfo Database Record (c) 2022 APA, all rights reserved)
Keywords: Drug Therapy; Effect Size (Statistical); Mental Disorders; Meta Analysis; Psychotherapies; Psychotherapy; Substance Use Disorder; Treatment Effectiveness Evaluation; effect sizes; efficacy; mental disorders; meta‐ analyses; pharmacotherapies; randomized controlled trials